Phát triển bền vững trong kinh tế chia sẻ: Khám phá vai trò của năng lực marketing từ chủ sở hữu nền tảng - Trần Thị Hoàng, Hà; Vũ Tuấn, Dương (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
This study applies the perceived value theory to examine the role of platform owners’ marketing capabilities in influencing service providers’ intention to continue using the platform within the context of the sharing economy. Based on survey data collected from 291 restaurants operating on online food delivery platforms, structural equation modeling using the partial least squares (PLS-SEM) method reveals that marketing capabilities significantly enhance epistemic value, social value, and continuance intention. Furthermore, continuance intention is predicted by economic value, social value, and epistemic value. In the relationship between marketing capabilities and continuance intention, social and epistemic values are confirmed as mediating variables. However, the impact of marketing capabilities on economic value is not supported, and economic value does not serve as a mediator as initially expected. Based on these findings, several implications are proposed for stakeholders to promote the sustainable development of sharing economy models.